Virtual Coast Guard: An Open and Crowdsourced GIS Portal for Stewardship of India's Coast. Issue 4 (17th October 2013) - Gajbe, Alpesh; Shankar, Adya; Rodriguez, Sudarshan
Abstract India's coastline is under tremendous pressure. The current processes of development are becoming a threat to the ecology and livelihoods housed on the coast. If left unchecked, there will not be much of a coast left for our future generations. GIS provides tremendous opportunities to map spatial information for better decision‐making. Government agencies generate maps, but they are localized and inaccessible, preventing an actual assessment of the damage that is already happening to our coast. The Coastal Area Mapping Project (CAMP) envisions creating a collaborative GIS platform using open source technologies. CAMP's vision is to use Free and Open Source Software (FOSS) for collaboration and cocreation and collective problem solving. CAMP foresees a vision for India's coastline where power is equalized among all constituencies (Government, corporations, media, communities, civil societies, etc.), by capturing the big picture and patterns, thus enabling the creation of strategies for stewardship of India's coastline for human wellbeing, coastal protection and sustainable coastal development.